Amniotic band syndrome: a diagnostic dilemma - Priya, Pritti K.; Aggarwal, Rohina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Amniotic band syndrome can cause a broad spectrum of anomalies ranging from simple band constrictions to major craniofacial and visceral defects. It occurs when the amnion is damaged during pregnancy. Thin strands of tissue called amniotic bands form inside the amnion and can tangle around the developing fetus, restricting blood flow, thus affecting the growth of certain body parts. This can cause congenital deformities of limbs, and if vital organs are involved, it can result in significant neonatal morbidity. A 25-year-old primigravida was referred for fetal karyotyping as the targeted anomaly scan revealed bilateral limb defects along with a single umbilical artery. The right foot was reported as lymphedema, and the left foot showed clubfoot deformity. Here, we report a case of amniotic band syndrome, which was missed for “Milroy’s primary congenital lymphedema” in antenatal sonography but was revealed in fetal autopsy. Mostly, amniotic band syndrome is diagnosed after birth, but with the advancement of ultrasound, prenatal diagnosis is possible. Also, three-dimensional ultrasound and magnetic resonance imaging can be used for a more detailed and accurate diagnosis. Accurate diagnosis is very important for further management of the pregnancy and in counselling regarding recurrences in future pregnancies.